โมเดลเชิงสาเหตุของการปฎิบัติงานแบบกลุ่ม : อิทธิพลของบุคลิกภาพห้าองค์ประกอบ ส่งผ่านความรู้เกี่ยวกับการทำงานแบบกลุ่ม บุคลิกลักษณะผัดวันประกันพรุ่ง และปฏิสัมพันธ์ - กุลชนา ช่วยหนู (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this research were (1) to develop and to validate the causal model of team-based performance mediating effects of five-factor personality via teamwork knowledge, trait procrastination, teamwork knowledge-trait procrastination interaction and (2) to investigate and to compare effects size, both direct and indirect effects, of five-factor personality, teamwork knowledge, trait procrastination, teamwork knowledge-trait procrastination interaction to team-based performance under Thai project team context. Participants were 525 primary school teachers, prathomsuksa 1-3, from Nakhon Si Thammarat Education Service Area Office 1 - 4 who were trained in the classroom action research methodology course. There were 4 research instruments: (1) Performance scale (2) The Knowledge, Skill, and Ability scale (3) Big Five scale (4) Trait Procrastination scale. Findings are as follows: (1) The causal model of team-based performance fits the empirical data. (2) Indirect and total effect of each five personality factors to team-based performance are significantly different from zero at alpha level .01. (3) Direct effect of teamwork knowledge to team-based performance is insignificantly different from zero. (4) Direct effect of trait procrastination to team-based performance is insignificantly different from zero. (5) Effect of each five personality factors to team-based performance is significantly decreased by level of teamwork knowledge-trait procrastination interaction.